Effect of different solvent extracts on the yield and in vitro antibacterial activity, with GC-MS analysis of active extracts from Vernonia amygdalina leaves - Mustafa, Nur Farid Amirul; Salleh, Mohd Syahmi; Noor Hashim, Noor Haslinda (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2024)
Vernonia amygdalina(V.amygdalina), commonly known as ‘Bitter leaf’, is a small perennial shrub with various medicinal properties including the treatment of stomach disorders, fever symptoms, diabetes, hypertension, and coughs. V.amygdalinais a potent source of antibacterial properties that may be beneficial in preventing bacterial infections and associated diseases such as fever and diarrhoea. V. amygdalinahas been extensively studied for its antioxidant, anti-inflammatory, antifungal, anticancer and antidiabetic properties. Although existing literature emphasises the importance of selecting appropriate extraction solvents to preserve the quality and therapeutic properties of V. amygdalina, the ideal solvent for maximum extraction of bioactive components remains unclear. Aim:The present study aims to determine the most efficient solvent for producing antibacterial-rich V. amygdalinaextracts. Methodology:Dried leaves of V. amygdalinawere extracted using various solvents (methanol, ethanol, and dichloromethane) to assess the extraction yield. The antibacterial potential of all extracts against Staphylococcus aureus, Escherichia coliand Pseudomonas aeruginosawas evaluated using the agar disc diffusion assay. The profiling of the active extract was accomplished using gas chromatography coupled with mass spectrometry (GC-MS). Results:Among the solvents tested, ethanol exhibited the highest extraction productivity, with a percentage yield of 49.20%. However, the findings of this study revealed that dichloromethane is the most efficient solvent for extracting antibacterial compounds from V. amygdalina leaves, with the inhibition zones against all bacteria strains ranging from 16.67 ± 1.20 mm to 21.33 ± 0.5 mm at 200 mg/mL. The GC-MS analysis of the dichloromethane extract identified compounds such as phytol, flavonoids, vitamin E, and squalene. Conclusion:The choice of the extraction solvent greatly affects the antibacterial efficacy of V. amygdalina leaves. The efficacy of V. amygdalinaagainst pathogenic bacteria strains demonstrated in this study highlights its potential for further exploration in pharmaceutical applications.